Degradation of surfactants from domestic laundry effluent by electron beam irradiation - Selambakkannu, Sarala (2021)
Surface active agent (surfactant) is the main ingredient in laundry detergent and other household cleaning agent. TWEEN20 is one of the nonionic surfactant which is widely used in detergent. Laundry effluent is one of the major contributor of domestic wastewater as laundering processes involves water-washing. Surfactant enters the environment when the effluents discharged into surface water and through sludge disposal on land. In order to protect the water bodies from any severe pollution, the effectiveness of high-energy ionizing radiation on decomposition of targeted surfactants, TWEEN20 from domestic laundry effluent at different operating condition were examined in this study. The experimental work was divided into two parts, part I verified the present of surfactants in laundry effluent using powdered and liquid detergents which will be collected from different sampling station. Whereas, part II involved the degradation of targeted pollutants by ionizing radiation technique. Two different type of laundry effluent was collected one using powdered detergent and another one using liquid detergent for fifteen days. Prior to irradiation, the characteristics of the water samples was analyzed in term of chemical oxygen demand (COD), total organic carbon (TOC), pH, and turbidity. Electron beam irradiation (EBI) was able to remove 100% of the TWEEN20 surfactant from laundry effluent for both liquid and powder detergent. The results obtained showed that electron beam irradiation is a very efficient and promising technology for the treatment of laundry effluent.